2007
DOI: 10.1002/cne.21416
|View full text |Cite
|
Sign up to set email alerts
|

Choline acetyltransferase‐immunoreactive neurons in the retina of normal and dark‐reared turtle

Abstract: Visual deprivation alters retinal-ganglion-cell response properties through changes in spontaneous wave-like activity (Sernagor and Grzywacz [1996] Curr Biol 6:1503-1508). This activity depends on cholinergic synaptic transmission in the turtle retina (ibid; Sernagor and Mehta [ 2001] J Anat 199:375-383). We studied the expression of choline acetyltransferase (ChAT) by immunocytochemistry and Western blot in developing retinas of control and dark-reared turtles. At postnatal day 0 (P0), right after hatching, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 60 publications
1
7
0
Order By: Relevance
“…We also included mouse brain as an additional control. The ChAT antibody used in this study has been shown previously to detect a single 68-70 kd band in turtle retina (Lee et al, 2007). In agreement with that study, we detected a prominent band of the appropriate size (73 kDa) in both turtle brain and ear (Fig.…”
Section: Chat Immunohistochemistry In the Turtle Cristasupporting
confidence: 92%
See 1 more Smart Citation
“…We also included mouse brain as an additional control. The ChAT antibody used in this study has been shown previously to detect a single 68-70 kd band in turtle retina (Lee et al, 2007). In agreement with that study, we detected a prominent band of the appropriate size (73 kDa) in both turtle brain and ear (Fig.…”
Section: Chat Immunohistochemistry In the Turtle Cristasupporting
confidence: 92%
“…Within the auditory and vestibular system, AB144P has been characterized in the inner ear of lizard (Wibowo et al, 2009), mouse (Kong et al, 2002), rat (Kong et al, 1994b), and human (Kong et al, 1994a(Kong et al, , 1998. This ChAT antibody has been shown by western blot to detect a single 68-70 kd band in turtle retina, as well as the brains of fish, lizards, and rat (Anad on et al, 2000;Lee et al, 2007;Wibowo et al, 2009). In our hands, we detected a doublet of bands via western blotting at 70 kd in turtle or a single band with mouse brain tissue extracts running at a slightly higher MW (Fig.…”
Section: Antibody Characterizationmentioning
confidence: 99%
“…Their arrangement into mosaics is thought to help neuronal cell types cover the retinal surface evenly and represent visual space homogeneously (Masland, 2001; Wassle, 2004). To what extent activity regulates the formation and maintenance of mosaics is incompletely understood (Zhang et al, 2005; Lee et al, 2007; Anishchenko et al, 2010). We analyzed the lateral distribution of two representative cell types in the inner retina.…”
Section: Resultsmentioning
confidence: 99%
“…1c). Finally, we examined the cholinergic amacrine cells, a cell type that has been reported to increase (Lee et al,2007) or decrease (Zhang et al,2005) in number in response to dark‐rearing. Neither the cholinergic amacrine cells in the ganglion cell layer (GCL), nor those in the inner nuclear layer (INL), differed significantly in their numbers between the control and dark‐reared animals (Fig.…”
Section: Resultsmentioning
confidence: 99%